(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
From the body in need of redesign I move to another body;a body remade to the point of completely having to be re-conceptualised. Thisis a body that is always open for new forms to take shape; a body that eschewshierarchical organisation of itself: Deleuze’s and Guattari’s (D&G) bodywithout organs (BwO). In looking at the BwO I endeavour to incite the reader tothink in different ways; similarly to what I think D&G urge us to do, thatis, to think differently, to open the body to new connections, to look atthings in a more sideways fashion, which is in an unusual and, at times, crazymanner.